Moor culture in independent Ceylon: the Moors Islamic Cultural Home (MICH) in the 1940s - Haniffa, F.F. (University of Colombo, 2017)
Sri Lankan Muslim leaders and social movements have constantly negotiated their connection to the global Muslim Umma with their place as a minority within the Sri Lankan polity. While Sri Lankan Muslim leaders have always taken pride in their connection to the global Muslim community, the manner in which such a community was imagined and the mode of engagement with such a community has shifted. It has varied in keeping both with national politics and changes in the larger Muslim world. This paper will address the creation of the Moor’s Islamic Cultural Home (MICH) as indexing a particular form of Muslimness that suited the manner in which the Sri Lankan polity was being imagined while anticipating independence. The founders wanted the institution to celebrate the glories of a global Muslim heritage, and drew connections to the intellectual centres of Alhambra, Baghdad, and Cordova, as well as to the scholarly, artistic, and spiritual prowess of Avicenna, Averroes, Al Ghazzali, and Rumi. Locally, they were concerned with asserting the particularity of a section of the Muslim community by naming themselves “Moors”. Additionally, they asserted Muslim specificity through establishing their own cultural institution but also represented Muslims as partaking of the same modernity to which the country as a whole was aspiring. However, the founders committed to ensuring that the state was involved and recognized Muslims’ (Moors’) contribution to the country’s economy and social life. The paper will also argue that in asserting Muslims’ Sri Lankaness, the institutions’ founders were rendering Muslims recognizable as partaking in middle and upper class ‘sociality’ through engaging in ‘recreation’ and entertainment in the atmosphere of an exclusive ‘club’. They were engaged—together with other communities building similar institutions—in the formation of ‘cosmopolitan’ elite post-colonial subjectivities.
Keywords: Muslims, Islam, identity, nationhood, cosmopolitanism